2020
DOI: 10.3390/ani10061071
|View full text |Cite
|
Sign up to set email alerts
|

Illustration of Different Disease Transmission Routes in a Pig Trade Network by Monopartite and Bipartite Representation

Abstract: Besides the direct transport of animals, also indirect transmission routes, e.g., contact via contaminated vehicles, have to be considered. In this study, the transmission routes of a German pig trade network were illustrated as a monopartite animal movements network and two bipartite networks including information of the transport company and the feed producer which were projected on farm level (n = 866) to enable a comparison. The networks were investigated with the help of network analysis and formed the ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 48 publications
0
16
0
Order By: Relevance
“…A recent study developed a new mathematical model to reconstruct the between-farm PRRSV dynamics, revealed the role of between-farm pig movements, indirect contacts by farm-to-farm proximity, and the continued circulation of PRRSV within infected sites (re-break) (Galvis et al, 2021). Despite the promising results, the study did not fully consider indirect contacts formed by the between-farm transportation vehicles networks, which has been previously described as one the major modes of the between-farm transmission of disease in swine (Büttner and Krieter, 2020; Porphyre et al, 2020; Niederwerder, 2021), and also in other systems such as cattle (Yang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…A recent study developed a new mathematical model to reconstruct the between-farm PRRSV dynamics, revealed the role of between-farm pig movements, indirect contacts by farm-to-farm proximity, and the continued circulation of PRRSV within infected sites (re-break) (Galvis et al, 2021). Despite the promising results, the study did not fully consider indirect contacts formed by the between-farm transportation vehicles networks, which has been previously described as one the major modes of the between-farm transmission of disease in swine (Büttner and Krieter, 2020; Porphyre et al, 2020; Niederwerder, 2021), and also in other systems such as cattle (Yang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Detailed data about the flux of transportation vehicles coming in and out premises can be difficult to obtain, which indeed explain lack of mathematical models considering this transmission pathway (Bernini et al, 2019; EFSA Panel on Animal Health and Welfare (AHAW) et al, 2021). Yet, previous studies have approached indirect transmission by transportation vehicles, such as the studies by Thakur et al, 2015 and Wiltshire, 2018, using probabilities to define indirect contact between farms (Thakur, Sanchez et al, 2015; Wiltshire, 2018), or the study by Buttner, 2020 that used observed truck movements between pig farms in Germany (Büttner and Krieter, 2020). The networks formed by transportation vehicles have been also described earlier as potential transmission routes of PRRSV (Dee et al, 2002; Dee et al, 2004; Pitkin et al, 2009; Thakur, Sanchez et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations